2006
DOI: 10.1080/02643290542000076
|View full text |Cite
|
Sign up to set email alerts
|

Social-perceptual abilities in adolescents and adults with Williams syndrome

Abstract: People with Williams syndrome (WMS) have a unique social phenotype characterised by unusually strong interest in other people and an engaging and empathic personality. Two experiments were designed to test whether this phenotype is associated with relatively spared abilities to decode mental-state information from nonverbal cues. The first experiment involved a modified version of the revised Eyes Test. The second experiment probed the ability to label emotions from brief dynamic facial displays. Adolescents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 25 publications
7
43
0
Order By: Relevance
“…And again, WS individuals may have used their superior vocabularies to pass this task. In any case, research also exists to suggest that emotion perception abilities in WS are commensurate with their general level of intellect (Plesa-Skwerer et al 2006;Porter 2004).…”
Section: Choice Of Tom Measuresmentioning
confidence: 95%
“…And again, WS individuals may have used their superior vocabularies to pass this task. In any case, research also exists to suggest that emotion perception abilities in WS are commensurate with their general level of intellect (Plesa-Skwerer et al 2006;Porter 2004).…”
Section: Choice Of Tom Measuresmentioning
confidence: 95%
“…The ability to ascribe such 'mental states' to others is critical for understanding others' minds and therefore adapting our own behaviour. Tager-Flusberg, Boshart and Baron-Cohen (1998) and Plesa Skwerer et al (2006b) have explored mental state understanding in WS using the 'Reading the Mind from the Eyes' task (Baron-Cohen, Wheelwright, Hill, Raste, & Plumb, 2001) and report variable findings (due to differences across studies in task design, see Riby & Back 2010 for discussion) but importantly both show that performance is below that expected by CA in typical development. In research using more ecologically valid whole faces expressing different mental states, and linking directly to the task used in the current study, Riby and Back (2010) showed that when the whole face was available for interpretation individuals with WS were proficient at processing mental states but that they were largely relying on the eye region to do so, when the eye region became uninformative through computer manipulation performance significantly reduced for individuals with WS compared to those developing typically.…”
Section: Processing Emotions In Ws: Basic and Complex Expressionsmentioning
confidence: 99%
“…Studies of emotion recognition have revealed performance at the level of age-and IQ-matched controls using face stimuli [ 52 ] and faces and voices [ 53 ]. In addition, whereas individuals with WS show empathy, they have diffi culty with more complex social cognitive tasks, such as theory of mind, performing only at mental age level [ 52 ].…”
Section: Social Cognitionmentioning
confidence: 99%